Koproses Karagenan-Pragelatinasi Pati Singkong Propionat sebagai Eksipien Sediaan Tablet Mengapung - Junaedi, .; Iskandarsyah, .; Anwar, Effionora (Indonesian Research Gateway)
The aim of this study was to prepare floating tablet dosage forms using coprocessed of kappa and iota carrageenan and pregelatinized cassava starch propionate (PPSP) as excipients. In this study, tablets were made by wet granulation method and using famotidine as a model drug. Several formulations of floating tablets were prepared using varying composition of the excipients coprossed carragenan with a certain ratio. The swelling and bupyancy of the floating tablets were evaluated. Furthermore, the drug release from the floating tablets were studied and analyzed using several models of kinetic equations. The result showed that formula A with excipients coprocessed carragenan (1:1) as much as 60% with 10% HPMC produce the best formula with floating lag time 11.42±1.53 minutes and total floating time for 22 hours. The formula also revealed a profile of controlled drug release and approached to Higuchi kinetics model and the non Fickian diffusion mechanism.Keywords : carragenan, PCSP, coprocess exipients, floating tablets.